2020
DOI: 10.1007/s40519-020-01081-5
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life assessment in eating disorders: adjustment and validation of a specific scale with the inclusion of an interpersonal domain

Abstract: Purpose Quality of life is a fundamental aspect of both clinical practice and research on eating disorders (ED) due to the significant impacts these disorders have on everyday life. Disorder-specific scales can improve the quality of research and findings and offer greater sensitivity and responsiveness. However, no specific instrument is available in Italian for ED. The aim of this paper is to adjust and to validate a reliable scale with specific items regarding physical and interpersonal well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 72 publications
(86 reference statements)
3
8
0
Order By: Relevance
“…The findings add new information regarding the association between the presence of NES and poorer HRQoL in the general population. Although this relationship has received relatively less research, several previous studies have explored the potential relationship between HRQoL and eating disorders, including anorexia nervosa, bulimia nervosa, binge eating disorder, and other specified feeding and eating disorders [ 8 ]. Past literature has generally suggested that HRQoL is poorer in individuals with eating disorders, with some studies indicating long-term impairments [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings add new information regarding the association between the presence of NES and poorer HRQoL in the general population. Although this relationship has received relatively less research, several previous studies have explored the potential relationship between HRQoL and eating disorders, including anorexia nervosa, bulimia nervosa, binge eating disorder, and other specified feeding and eating disorders [ 8 ]. Past literature has generally suggested that HRQoL is poorer in individuals with eating disorders, with some studies indicating long-term impairments [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that different types of eating disorders have been shown to significantly impact the quality of life (QoL) of individuals, in which people with symptoms of eating disorders exhibit noticeably lower QoL, relatively few studies investigated the relationship between NES and QoL [ 7 ]. Quality of life is a comprehensive concept referring to individuals’ satisfaction with their health and functioning across different aspects of life, including the physical, mental, cognitive, and social domains [ 8 ]. Specifically, health-related quality of life (HRQoL) encompasses areas of QoL that reflect an array of health status indices specific to physical, psychological, and social dimensions of health [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The EDE-Q generates a total score and four subscales: Restraint, Eating Concern, Shape Concern, and Weight concern. The Italian Eating Disorder Quality of Life test (IEDQOL) is a 33-item scale rated on a five-point Likert scale and was used to assess the healthrelated quality of life perceived, with higher scores indicating poorer quality of life (Meneguzzo et al, 2020b).…”
Section: General and Specific Psychopathologymentioning
confidence: 99%
“…Despite differences in their clinical manifestations, people with eating disorders (EDs) often experience interpersonal problems and difficulties with social cognition that negatively affect their social functioning, quality of life, and daily activities [ 1 , 2 , 3 , 4 , 5 ]. Different psychological elements have been related to dysfunctional eating behaviors and interpersonal difficulties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%